Sisters and Lovers: Women and Desire in Bali - Jennaway, Megan (Rowman & Littlefield Publishers, 2002)
The Balinese devotion to their temples is both legendary and conspicuous, but the ways in which they enshrine their innermost desires have long been hidden. This ethnography draws back the veil by focusing on the romantic experiences of women in a rural village (Punyanwangi) in North Bali from adolescence to maturity. Delving into the intensity of passion that exists just below the harmonious veneer of traditional patterns of courtship and marriage, motherhood, and connubial fidelity, this book overturns Margaret Mead's assertions of passivity in Balinese social life. Punyanwangi's proximity to a thriving tourist center allows Megan Jennaway to explore as well the striking gender disparities in the ways sexuality and desire are culturally mediated. Aside from service work, women are excluded from entering the tourist domain, yet male sexual adventurism is expected and even encouraged. The bodies of foreign women are thus invested with potent fantasies of exotic desire, while those of local women are muted-denied legitimate avenues of expression. The author invokes Post-Freudian and feminist concepts of sexuality to explain culturally specific psychiatric disorders to which Balinese women are prone, interpreting them as expressions of frustrated desire. She thus convincingly reveals Balinese society as anything but unemotional or stagnant. Rather, it is swept along by currents of emotionally charged desire. By allowing key informants to tell their stories in their own voices and by skillfully interweaving fictionalized interludes, the author gives us not only a rigorously researched ethnography, but an intimate and fully realized portrait of Balinese women's innermost desires.